Relationship between reactive oxygen species production in human semen and sperm DNA damage assessed by Sperm Chromatin Structure Assay - Novotný, Jiří; Aziz, Nabil; Rybář, Roman; Březinová, Jana; Kopecká, Věra; Filipčiková, Radka; Řeřuchová, Marie; Oborná, Ivana (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2013)
AIM: The aim of this prospective study was to find possible relationship between ROS production measured by chemiluminescence and flow cytometry in human semen and sperm DNA damage estimated by Sperm Chromatin Structure Assay. METHODS: Study included 39 men from infertile couples and 23 fertile volunteers who served as a control group. Aliquot of neat semen was used for ROS detection by chemiluminescence. Aliquot of sperm suspension in phosphate buffered saline was used for the detection of ROS by flow cytometry. Another aliquot of sperm suspension was used for SCSA to measure DNA fragmentation index and High DNA stainability. RESULTS: DNA fragmentation index correlated negatively with sperm morphology and motility. High DNA stainability correlated positively with ROS production and negatively with sperm morphology and concentration. Although there were similar trends of rising DNA fragmentation index and ROS production among the three groups of men, the relationship did not reach statistical significance. CONCLUSIONS: Higher values of DNA fragmentation index and high DNA stainability may also reflect developmental and/or environmental problems and not only oxidative stress.
Keywords: dospělí; genetické techniky; DNA Damage; spermie; Adult; Semen; Chromatin; Spermatozoa; lidé; Reactive Oxygen Species; sperma; poškození DNA; prospektivní studie; Male; Prospective Studies; chromatin; Genetic Techniques; reaktivní formy kyslíku; mužské pohlaví; Humans